The role of protective factors and the relationship with recidivism for high-risk young people in detention - Shepherd, Stephane M. (Criminal justice and behavior, 2016)
This study sought to ascertain the prevalence of protective factors and association with client risk level and future offending in a sample of 177 Australian youth in detention. The Protective Domain on the Structured Assessment of Violence Risk in Youth (SAVRY) instrument was utilized to identify protective items in the cohort. The mean number of protective factors for the entire sample was low (under two) with higher risk clients averaging less than one current protective item. Although the number of protective factors engendered criminal desistance, this effect did not extend to the highest risk young offenders. Clients who re-offended were significantly less likely to present with five out of the six SAVRY protective items. In addition, pro-social involvement and school engagement had the strongest associations with non re-offense. Clinical implications for client risk management are discussed.